أهم معايير الجودة للمنتجات المرئية للأشخاص الصم - الزهراني، أحمد عبدالله (جامعة البحرين - مركز النشر العلمي, 2023)
يهدف البحث الحالي إلى معرفة أهم المواصفات والمعايير الواجب توافرها في أي منتج مرئي لمجتمع الصم. إضافة إلى التعرف على مدى رضا الأشخاص الصم عن أهم معايير المحتوى المرئي والإخراج والترجمة المناسبة عند تصميم وإعداد البرامج والمقاطع المرئية للأشخاص الصم. ولتحقيق أهداف هذا البحث استعمل المنهج الوصفي المسحي، وتم بناء المقياس بصورته النهائية بعد استكمال شروطه من صدق وثبات وقوة تمييزية، وكان عدد فقراته (40) فقرة، موزعة على ثلاثة محاور، تكونت عينة البحث من 31 مشاركا ومشاركة من الأشخاص الصم وضعاف السمع الأعضاء في الجمعية السعودية للإعاقة السمعية للصم مدينة الرياض. النتائج أظهرت مدى رضا الأشخاص الصم عن عدد من المعايير المهمة عند تصميم أي عمل مرئي للأشخاص الصم، منها ما يتعلق بالمحتوى واللغة المستخدمة، وأن يتضمن الإخراج عددا من الاشتراطات مثل الإضاءة وحجم صورة المترجم، وحجم الخط للنص الكتابي، والألوان والخلفية. وضرورة استخدام الترجمة الاحترافية. The present study aims to know Deaf people's satisfaction level concerning the most important specifications and standards that should be present in any visual product for the Deaf people. It also seeks to identify the most important sports activities preferred by the deaf, and their impact on their quality of life. To achieve the objectives of this research, the descriptive survey method was used. The scale was built in its final form after completing its conditions i.e. validity, stability and discriminatory power. The number of its paragraphs was (40), divided into three axes. The current study consisted of 31 deaf participants who are members of the Saudi Society for Hearing Impairment in Riyadh. The results of the study showed that there is a level of satisfaction of deaf people with some criteria of designing and preparing any visual work for Deaf people, including the content provided and the language used. In addition, the final output of the product should include a number of requirements before broadcasting such as lighting, the size of the interpreter's appearance on screen, the size of the font of closed caption, colors and background. The study also found the importance of using professional interpretation to suit the levels of all deaf people.
Keywords: ذوي الاحتياجات الخاصة -- الإعاقة السمعية -- المحتوي المرئي -- معايير الجودة -- السعودية